2013
DOI: 10.1111/bph.12268
|View full text |Cite
|
Sign up to set email alerts
|

The additional ACh binding site at the α4(+)/α4(−) interface of the (α4β2)2α4 nicotinic ACh receptor contributes to desensitization

Abstract: BACKGROUND AND PURPOSENicotinic ACh (α4β2)2α4 receptors are highly prone to desensitization by prolonged exposure to low concentrations of agonist. Here, we report on the sensitivity of the three agonist sites of the (α4β2)2α4 to desensitization induced by prolonged exposure to ACh. We present electrophysiological data that show that the agonist sites of the (α4β2)2α4 receptor have different sensitivity to desensitization and that full receptor occupation decreases sensitivity to desensitization. EXPERIMENTAL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 36 publications
(90 reference statements)
4
28
0
1
Order By: Relevance
“…Assuming a translation of the in vitro window current to an in vivo setting, such a persistent cholinergic activity could likely be a contributing phenomenon in volume transmission. Here, the wider window current at lower ACh concentrations observed with HS receptors [22,23] especially supports a role for this stoichiometry in this transmission mode.…”
Section: Modes Of Neurotransmission Of A4b2 Nachr Stoichiometriessupporting
confidence: 64%
See 4 more Smart Citations
“…Assuming a translation of the in vitro window current to an in vivo setting, such a persistent cholinergic activity could likely be a contributing phenomenon in volume transmission. Here, the wider window current at lower ACh concentrations observed with HS receptors [22,23] especially supports a role for this stoichiometry in this transmission mode.…”
Section: Modes Of Neurotransmission Of A4b2 Nachr Stoichiometriessupporting
confidence: 64%
“…It is thus believed to relate to the residual nAChR activity in a scenario of tonic exposure to an agonist, such as in volume transmission as described below, or upon administration of an exogenous nicotinic agonist. Here, it has been observed that the HS stoichiometry displays window current at lower and presumably more physiological agonist levels than the LS receptor [22,23]. Analogously, the window currents for various a4b2* agonists differ between the two stoichiometries [24].…”
Section: Molecular Aspects Of Nachrsmentioning
confidence: 72%
See 3 more Smart Citations